If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2f+3=-f
We move all terms to the left:
-2f+3-(-f)=0
We add all the numbers together, and all the variables
-2f-(-1f)+3=0
We get rid of parentheses
-2f+1f+3=0
We add all the numbers together, and all the variables
-1f+3=0
We move all terms containing f to the left, all other terms to the right
-f=-3
f=-3/-1
f=+3
| 19x+15=8x+15 | | -2/3u-9/7=-1/2 | | -7a+1=50 | | z/4=z+7/6 | | Y=4x+2;(5,-3) | | 3–5(2x+1)=3(3+x) | | z/4=7+z/6 | | z/4=7z/6 | | 158+a=180 | | -3(4x-8)=-60 | | X+3x+8=18-x+30 | | 3u+3=-18 | | 12(4+x)+5(-2x-9)=17 | | 8+3x=1/2(16+6) | | 8/5w2=160 | | 3(-4/3)-y=-4 | | 2x-15=41 | | 3u3=-18 | | 5(y-2)=-32 | | 10q=10+5q | | 10w=6w+32 | | .8x=50 | | 5(4+2x)-4(2x-3)=40 | | -21=-6+5w | | 2.9+0.01x=0.3x | | 4a+1/10a=3/8 | | 2^2×+9^2y=55 | | (1/9^x)+(1/3^x)=6 | | -20=3u-2 | | 3(y-2)-4y=2(y-9 | | x2–25=6x–9 | | 9=-2(a+4)9a |